Pengaruh Belanja Modal Terhadap Indeks Pembangunan Manusia Melalui Pertumbuhan Ekonomi Sebagai Variabel Intervening Provinsi Bali - Setiawan, Gusi Bagus Kompiang Putra; Budiana, Dewa Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 10, Oktober 2015 (pp.1194-1327), 2015)
Human development index is one of the many variables used to measure people’s welfare. The vast difference between people’s welfare causes inequality among regions. Through government policy, as in increasing government spending on capital, increases people’s welfare, economic growth and also contributes in raising the quality of human development index. Using Path Analysis, this study is conducted to find out the impact of government’s capital expenditure on human capital index through economic growth as intervening variable on Bali during 2008-2013.The result shows that: 1) Government’s capital expenditure has positive and significant impact on economic growth, 2) Economic growth has positive and significant impact on human development index, 3) Capital expenditure has positive and significant impact on human development index, and, 4) Spending on capital has indirect effect on human development index through economic growth as mediator. This is shown by the value of z-statistic 4,35 which larger than the value of z-table 1,96. It means that economic growth is mediating variables.
Keywords: Belanja Modal, Pertumbuhan Ekonomi, Indeks Pembangunan Manusia